2012
DOI: 10.1080/10255842.2010.550887
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of medial collateral ligament repair: migration, fibroblast proliferation and collagen formation

Abstract: The partial rupture of ligament fibres leads to an injury known as grade 2 sprain. Wound healing after injury consists of four general stages: swelling, release of platelet-derived growth factor (PDGF), fibroblast migration and proliferation and collagen production. The aim of this paper is to present a mathematical model based on reaction-diffusion equations for describing the repair of the medial collateral ligament when it has suffered a grade 2 sprain. We have used the finite element method to solve the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this sense, much effort is directed towards representing remodelling in vascular tissue [40][41][42][43], with a particular focus on the pathological remodelling observed in aortic aneurysm tissue [44][45][46]. The mathematical modelling of the inflammation, proliferation and remodelling phases in ligament tissue has also been addressed [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, much effort is directed towards representing remodelling in vascular tissue [40][41][42][43], with a particular focus on the pathological remodelling observed in aortic aneurysm tissue [44][45][46]. The mathematical modelling of the inflammation, proliferation and remodelling phases in ligament tissue has also been addressed [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…2. Enhance the proliferation of human gingival fibroblasts thereby promoting and stimulating periodontal soft tissue repair [17][18][19] .…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Animal experiments [38,39] and clinical studies [40,41] showed that PRP could promote bone regeneration, mandibular reconstruction and wound healing of periodontal root bifurcation and bone defects. In vitro studies have shown that PRP can stimulate the proliferation and differentiation of fibroblasts, osteoblasts, mesenchymal stem cells (MSCs) and periodontal ligament cells, and induce bone defect repair and periodontal tissue regeneration [42,43]. It also stimulates the proliferation of fibroblasts and induces collagen synthesis, showing beneficial effects on wound healing [44].…”
Section: Biological Effects Of Prp On Periodontal Bone Regeneration (...mentioning
confidence: 99%